(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
The pattern of education in pesantren is very close and well applied to the world of education, this certainly makes the pesantren curriculum combined with the national curriculum. The current pattern of education is still a mistake in responding to the education system. The purpose of this study is to describe the role of a combination of pesantren education patterns and general education in shaping religious character and to determine the dynamics of educational patterns in dealing with educational problems within the scope of Islamic boarding schools. This study used descriptive qualitative research, data subjects totaled 2 people (1 kyai hut leader and 2 students). 1 Kyai to obtain the pattern of education applied by pesantren and the dynamics that occur, with 2 students to obtain information about the implementation of education and responses to the pattern of education that has been applied. Data collection techniques use observation, interviews, and documentation. The data analysis technique uses Miles and Huberman (1984), digging and reviewing data until saturated data is obtained, which is done by collecting all data, then reducing the data, presenting data, and making conclusions. The results of this study show that: 1) The pattern of pesantren education and general education is very appropriate to be combined because the values contained in it can shape the religious character of students and students. 2) The dynamics that occur in the Islamic boarding school environment are a challenge for educational institutions, especially informal and formal institutions in instilling a good mindset for the community towards the pattern of education applied, because the attitude of the community in responding to a very sensitive problem, so that there tend to be pros and cons, even though this is only people involved in the event, the point of view of ordinary people in particular is respected to such educational institutions. Therefore, it is necessary to cultivate an educational mindset and continue branding by continuing to implement the best educational pattern to realize the religious character of students through the cultivation of suritauladan of lodge leaders such as kyai and seniors in exemplifying religious values in everyday life so that students with character will be realized.